Effect of Activated Human Protein C on Experimental Venous Thrombosis Induced by Stasis with Operative Invasion in Mice - Aoki, Yasunori; Fukumoto, Yuki; Inoue, Kyoko; Katsuura, Yasuhiro; Komoriya, Keiji; Miyamoto, Seiji (Arzneimittelforschung, 2000)
Protein C (PC) is the zymogen of an anticoagulant serine protease and is converted to its active form (activated protein C: APC) by thrombin in the presence of thrombomodulin. APC plays an important role in regulating blood coagulation and fibrinolysis by inhibiting not only blood coagulation factors Va and VIIIa but also type-1 plasminogen activator inhibitor (PAI-1).In this study, it was reported that the antithrombotic effect of a human APC product (designated as CTC-111) compared with that of heparin and human PC on the deep venous thrombosis (DVT) model induced in mice by stasis caused by inferior vena cava ligation and operative invasion. Drugs were injected into a tail vein at –2, 30, 60, and 120 min after the inferior vena cava ligation. One-fifth amount of the total dosage of a given drug was injected at each time point. The wet weight of thrombus formed was reduced by APC or heparin administration, however, PC, which was equal to APC in protein amount, did not show any antithrombotic effect.To confirm whether human PC could be activated by mouse thrombin, PC was treated with mouse or human thrombin to measure the amount of APC formed. Mouse thrombin could activate human PC at a similar activation rate as human thrombin.These results suggest that externally administrated PC cannot exhibit antithrombotic effect in this DVT model due to slow activation rate to APC and that APC is a better antithrombic agent than PC for treating thrombotic diseases.
Keywords: Activated protein C, effect on venous thrombosis, mouse; CTC-111; Plasminogen activator inhibitor; Protein C; Thrombin